2013
DOI: 10.17221/41/2012-pps
|View full text |Cite
|
Sign up to set email alerts
|

Systemic applications of azadirachtin in the control of Corythucha ciliata (Say, 1832)(Hemiptera, Tingidae), a pest of Platanus sp.

Abstract: AbstractsPavela R., Žabka M., Kalinkin V., Kotenev E., Gerus A., Shchenikova A., Chermenskaya T. (2013): Systemic applications of azadirachtin in the control of Corythucha ciliata (Say, 1832) (Hemiptera, Tingidae), a pest of Platanus sp. Plant Protect. Sci., 49: 27-33.In 2010 and 2011, the efficiency of azadirachtin, applied as systemic trunk injections in the trunks of Platanus sp., was tested against Corythucha ciliata. Azadirachtin in the doses of 0.1 and 0.05 g of active ingredient per cm of diameter at br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
1
9
0
1
Order By: Relevance
“…In another study injecting azadirachtin in the trunks of Platanus sp. under natural conditions, it was found that the density of nymphs and adults of Corythucha ciliata (Say, 1832) (Hemiptera, Tingidae) decreased significantly over 2 years compared to the control (Pavela et al, 2013). Similarly, azadirachtin was found to cause a high mortality of fourth instar nymphs in the present study.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In another study injecting azadirachtin in the trunks of Platanus sp. under natural conditions, it was found that the density of nymphs and adults of Corythucha ciliata (Say, 1832) (Hemiptera, Tingidae) decreased significantly over 2 years compared to the control (Pavela et al, 2013). Similarly, azadirachtin was found to cause a high mortality of fourth instar nymphs in the present study.…”
Section: Discussionsupporting
confidence: 57%
“…Azadirachtin gives useful control of insects that are resistant to synthetic pesticides. Azadirachtin is also an insect growth regulator (Isman, 2006;Saha et al, 2011;Pener & Dhadialla, 2012;Pavela et al, 2013;Sánchez-Ramos et al, 2014;Vacante & Kreiter, 2018;Joseph, 2019;Pamela, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Any ovicidal or nymphicidal effects on the overwintering eggs or emerging young instars can effectively suppress the population build-up later in the season. Previous studies showed that IGRs target the developing immature stages of several insect pests, such as azadirachtin, on Corythucha ciliata (Say) (Hemiptera: Tingidae) [25]; novaluron and methoprene on the storage pests Tribolium castaneum and T. confusum (Coleoptera: Tenebrionidae) [26]; novaluron and diflubenzuron on Bagrada hilaris (Burmeister) (Hemiptera: Pentatomidae) [27]; and pyriproxyfen on the sweet potato whitefly Bemisia tabaci (Gennadius) and the greenhouse whitefly Trialeurodes vaporariorum (Westwood) [19].…”
Section: Discussionmentioning
confidence: 99%
“…Leaf residue levels dropped rapidly after the first azadirachtin foliar spray, whereas azadirachtin showed a more uniform pattern of persistence in the trunk injected trees. This makes sense as the tree can store azadirachtin within leaf tissue as a metabolite without changing its biological effect [ 28 , 29 ]. Azadirachtin on the surface of the plant, however, breaks down quickly under ultraviolet light [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%